Work-Related Musculoskeletal Disorders and Their Associated Risk Factors among Pakistani Dental Practitioners: A Cross-Sectional Study. (10th May 2022) - Younis, Usman; Shakoor, Asma; Chaudhary, Farooq Ahmad; Din, Shahab Ud; Sajjad, Sadia; Younis, Maryiam; Javed, Muhammad Qasim; Alam, Mohammad Khursheed
Abstract : Background . Work-related musculoskeletal disorders (WMSDs) have a negative impact on quality of life, and dentists are at risk of WMSDs due to the nature of work being static, repetitious, and for a long duration. The study was aimed at measuring the prevalence and distribution of work-related musculoskeletal disorders and determining the risk factors associated with affliction among Pakistani dentists. Methods . An online cross-sectional survey was conducted using a validated questionnaire consisting of four sections. The first section had questions related to sociodemographic information, the second section had questions that assessed the intensity and frequency of musculoskeletal pain (MSP), third section questions were concerned with the effect of MSP on the respondents' daily life, while the last section contained questions on whether they perceived their work in the dental clinic as a cause of their pain. Chi-square and one-way ANOVA tests were used for the analysis of the data in SPSS-23. Results . A total of 600 completely filled questionnaires were received with a response rate of 76.4%, and about 87% of the dental practitioners had some sort of MSD. The intensity and frequency of WMSDs were statistically significant (p < 0.05 ) in association with all the sociodemographic characteristics. The lower back area was the most reported site of WMSD pain (51.3%) followed by the neck/upper back (21.3%) and shoulder (17.6%). The site of pain was statistically significant (p < 0.05 ) in association with all the sociodemographic characteristics except gender (p = 0.11 ). A majority of participants (95.4%) had sought medical treatment and taken sick leaves (70%) due to WMSDs pain during their life. Participants attributed a number of working years and working posture as the two main reasons behind WMSDs. Conclusion . Considering the high prevalence of WMSDs among dentists, preventive strategies that minimize the occurrence of WMSDs should be adopted by dental professionals. The impact of WMSDs can be reduced by maintaining good posture, taking breaks and rest in between work, doing regular exercise, and improving the work environment.